Peningkatan Kompetensi Numerasi Guru di SD Negeri Pedurungan Tengah 02 melalui Pembelajaran Numerasi Bermakna dengan Pendekatan UBD - Nuvitalia, Duwi; Muhtarom, Muhtarom; Sugiyanti, Sugiyanti; Endahwuri, Dhian (Pelita: Jurnal Pengabdian kepada Masyarakat, 2025)
The implementation of community service activities aims to improve the numeracy competency of teachers at SDN Pedurungan Tengah 02, especially in teaching mathematics with a more meaningful approach for students. Effective and enjoyable numeracy learning will help students understand the concepts and numerical skills that are essential in everyday life. One of the approaches implemented is Understanding by Design (UBD), which prioritizes in-depth conceptual understanding and the relevance of the material to students' real lives. This community service activity includes several stages, including intensive training for teachers on the concept and application of the UBD approach in numeracy learning, techniques for connecting material with students' real experiences to make learning more relevant and meaningful, and formative and diagnostic assessments of numeracy. Community service activities regarding meaningful numeracy learning through UbD can improve the competency of SDN Pedurungan Tengah 02 teachers as indicated by the results of the Pre-test and Post-test which have increased. This shows the teachers' understanding of Numeracy learning through UbD and how it is implemented.